Pharmacological activity of 6-Gingerol in Dextran Sulphate Sodium-induced ulcerative colitis in BALB/c Mice (2015)
Gingerols are phenolic compounds in ginger (Zingiber officinale), which have been reported to exhibit antiinflammatory, antioxidant, and anticancer properties. The present study aimed at evaluating the possible pharmacologic activity of 6-gingerol in a mouse model of dextran sulphate sodium (DSS)-induced ulcerative colitis. Adult male mice were exposed to DSS in drinking water alone or co-treated with 6-gingerol orally at 50, 100, and 200 mg/kg for 7 days. Disease activity index, inflammatory mediators, oxidative stress indices, and histopathological examination of the colons were evaluated to monitor treatment-related effects of 6-gingerol in DSS-treated mice. Administration of 6-gingerol significantly reversed the DSS-mediated reduction in body weight, diarrhea, rectal bleeding, and colon shrinkage to near normal. Moreover, 6-gingerol significantly suppressed the circulating concentrations of interleukin-1β and tumor necrosis factor alpha and restored the colonic nitric oxide concentration and myeloperoxidase activity to normal in DSS-treated mice. 6-Gingerol efficiently prevented colonic oxidative damage by increasing the activities of antioxidant enzymes and glutathione content, decreasing the hydrogen peroxide and malondialdehyde levels, and ameliorated the colonic atrophy in DSS-treated mice. 6-Gingerol suppressed the induction of ulcerative colitis in mice via antioxidant and antiinflammatory activities, and may thus represent a potential anticolitis drug candidate.